Photocatalytic α‐Tertiary Amine Synthesis via C−H Alkylation of Unmasked Primary Amines. (11th June 2020) - Ryder, Alison S. H.; Cunningham, William B.; Ballantyne, George; Mules, Tom; Kinsella, Anna G.; Turner‐Dore, Jacob; Alder, Catherine M.; Edwards, Lee J.; McKay, Blandine S. J.; Grayson, Matthew N.; Cresswell, Alexander J.
Abstract: A practical, catalytic entry to α, α, α‐trisubstituted (α‐tertiary) primary amines by C−H functionalisation has long been recognised as a critical gap in the synthetic toolbox. We report a simple and scalable solution to this problem that does not require any in situ protection of the amino group and proceeds with 100 % atom‐economy. Our strategy, which uses an organic photocatalyst in combination with azide ion as a hydrogen atom transfer (HAT) catalyst, provides a direct synthesis of α‐tertiary amines, or their corresponding γ‐lactams. We anticipate that this methodology will inspire new retrosynthetic disconnections for substituted amine derivatives in organic synthesis, and particularly for challenging α‐tertiary primary amines. Abstract : Catalytic strategies for the α‐C−H functionalisation of primary amines are a major challenge in organic synthesis. A photocatalytic protocol for the α‐C−H alkylation of unprotected primary amines that is amenable to the direct synthesis of α‐tertiary primary amines is reported. This process is readily scalable in continuous flow to provide access to decagram quantities of valuable γ‐lactams and azaspirocycles, for application in drug discovery.